NO THE HOLMBERG EFFECT FOR GALAXY PAIRS SELECTED FROM THE SDSS DR9 AT Z ≤ 0:06 - Dobrycheva, D. V.; Vavilova, I. B. (Одеські астрономічні публікації, 2016)
We studied the Holmberg effect in galaxy pairs selected from the SDSS DR9, where 60561galaxies were limited by redshift 0.02 < z < 0.06 and absolute magnitude: Mr ≤ −20.7 m for central galaxies (N=18578) and Mr > −21.5 m for neighbor galaxies (N=41983). We have made a morphological classification for each galaxy using both the visual inspection and machine learning methods. We considered four morphological types of galaxy pairs (E, early, and L, late, types) for testing the Holmberg effect: E- E, E-L, L-E, L-L (first companion of pairs is a central galaxy and second one is a faint satellite galaxy). We concluded about the absence of the Holmberg effect: Rg−i = 0.3 for L-E pairs at 0.04 < z ≤ 0.06 and Rg−i = 0.2 for E-E and E-L pairs at 0.02 ≤ z ≤ 0.04. Summarizing, a correlation of color indices in pairs for the samples of galaxies composed with the half of large sky surveys likely SDSS was not confirmed or confirmed partially. The Holmberg effect is rather connected with morphological types of galaxies than with their color indices. Taking into account a scenario of the secular evolution, the presence of at least one elliptical galaxy in pair may be indicator of previous mergers in the earlier epoch. So, figuring manifestations of the Holmberg effect in its original interpretation no longer seems such urgent.